Variable Gut Function Recovery After Right vs. Left Colectomy May Be Due to Rectosigmoid Hyperactivity - Seo, Sean Ho Beom; Bissett, Ian; O’Grady, Gregory (Frontiers in Physiology, 2021)
It is established that gut function recovers slower after right vs left colectomies with higher rates of prolonged post-operative ileus (PPOI) but the reason is unclear. Development of PPOI is multifactorial. A recent manometry study in right colectomy patients showed that the distal colon becomes hyperactive after surgery with predominantly cyclic motor patterns (CMPs). In this perspective, we evaluate the hypothesis that the slower gut recovery after right hemicolectomy could be induced by a functional obstruction due to hyperactive CMPs.